Clinoptilolite induces cell death in THP-1 cells in oxidative stress conditions: antioxidant and anticancer effect of clinoptilolite - Demircan, Gunnur; Ozdas, Sule Beyhan; Akin, Demet (Progress in Nutrition, 2020)
Aim: Zeolites are tectosilicates which appear as minerals in nature and can also be synthesized in thelaboratory conditions. Clinoptilolite is a natural zeolite which has ion exchanging and adsorbent characteristics. We have aimed to display the effect of clinoptilolite to apoptotic, autophagic and antioxidant characteristics of cancercell lines under oxidative stress conditions. Material and Methods: The cytotoxicity of clinoptilolite was evaluated using the MTT assay. The total antioxidant status was measured by the total antioxidant status (TAS) detection kit. The western blotting analysis was performed in order to assess the protein expression levels of the apoptosis and to autophagy markers like Beclin1, Bcl-2 and LC3B. Results: 24 hours incubation of cancer cells with clinoptilolite reduced cell proliferation in a dose dependent manner. Clinoptilolite lowered the autophagy in cancer cells, in particular, directing the cells towards apoptosis and leading to a fall in the TAS levels. Clinoptilolite to cause a decrease in antioxidant defence. Discussion: Parallel to these findings, it has been seen that there was an increase in apoptosis and a decrease in autophagy in cells induced with hydrogen peroxide effect. In this study, clinoptilolite was shown to cause a decrease in antioxidant defense.